ANTIBACTERIAL ACTIVITY OF Samanea saman LEAF ETHANOL EXTRACT AGAINST Escherichia coli AND Staphylococcus aureus AND ITS TOTAL FLAVONOID AND PHENOLIC CONTENTS - Rita, W. S.; Swantara, I M. D.; Astiti Asih, I. A. R.; Sinarsih, N.K. (Jurnal Kimia (Journal of Chemistry); Vol.12 No.2 Juli 2018, 2018)
Antibacterial activity of Samanea saman usually shows a positif correlation to the flavonoid and phenolic contents.  The aim of this study was to evaluate the antibacterial activity of the ethanol extract of Samanea saman against Escherechia coli and Staphylococcus aureus and determine the total flavonoid and phenolic contents of the extract. The extraction was done by ethanol 96% at room temperature. The antibacterial assay was conducted by agar disc diffusion method. The total flavonoid and phenolic contents were determined by UV-Vis Spectrofotometer with the standard of quersetin and galic acid, respectively. The extraction of 250 g of Samanea saman leaves resulted in 24.5 g of ethanol extracts. The ethanol extract showed a moderate inhibition of 8.33 mm towards E. coli and a strong inhibition of 13.6 mm towards S. aureus at the concentration of 4%. The Minimum Inhibitory Concentration (MIC) of the extract against E. coli and S.aureus were of 3% and 0.3%”, respectively. The total flavonoid and phenolic contents were successively 1233.2991 mg QE/100g and 2544.6154 mg GAE/100g. Keywords : Escherechia coli , flavonoid and phenolic content,   Samanea saman , S taphylococcus aureus